Urban food production limits and the viability of community gardens: The case of hartford, connecticut - Heidkamp, C.P.; Russell, S.E.; Sloan, M. (Local Food Systems in Old Industrial Regions: Concepts, Spatial Context, and Local Practices, 2012)
Hartford, the state capital of Connecticut, is a typical example of a former manufacturing oriented1 industrial city and, like much of the urban northeastern United States, has gone through a period of economic deindustrialization and consequent urban decay. Since the departure of the manufacturing base, Hartford has refocused its economic development on the service economy, and first and foremost, the insurance industry. The city even proclaims itself the “insurance capital of the world.” Yet, even though the insurance industry as well as other service oriented development strategies (a new convention center, science museum, and retail developments) have been quite successful in fostering economic activity and attracting employees (mostly residents of the surrounding suburbs commuting into white collar jobs), the spatial manifestations of deindustrialization are still visible and persistent in the physical as well as the social fabric of the city. © 2012 Neil Reid, Jay D. Gatrell and Paula S. Ross All rights reserved.
Keywords: dept.egm

Book Review: Responses to elizabeth j. mueller review of the city reader, 5th ed., and/or the american urban reader: history and theory - Wuerzer, Thomas; Wang, Jing; Klotz, Marilyn; Holt, William G. (Journal of Urban Affairs, 2012)
Keywords: book.review; dept.egm

Use of aguadas as water management sources in two southern maya lowland sites - Ferrand, Ezgi Akpinar; Dunning, Nicholas P; Lentz, David L; Jones, John G (Ancient Mesoamerica, 2012)
Aguadas, either natural or human-made ponds, were significant sources of water for the ancient Maya. Aguadas are common features in the Maya Lowlands and make valuable locations for collecting archaeological and paleoenvironmental data. This article discusses research conducted at four aguadas around two adjacent Maya sites, San Bartolo and Xultun in Peten, Guatemala. Both San Bartolo and Xultun were established during the Preclassic period. However, the fates of the two sites differed, as Xultun continued to prosper while the city of San Bartolo was abandoned near the close of the Late Preclassic period. We argue that aguadas provide important clues for understanding the fate of these two ancient communities and many others in the Maya Lowlands. Copyright © 2012 Cambridge University Press.
Keywords: Guatemala [Central America]; Maya Lowlands; Peten; San Bartolo; archaeological evidence; dept.egm; paleoenvironment; planning history; urban planning; water management; water resource; water use

Where to begin? Getting started teaching GIS&T - West, Eric (Teaching Geographic Information Science and Technology in Higher Education, 2012)
Keywords: Coordinating lectures; Exercise style; Faculty teaching GIS&T; Global positioning system; Global positioning systems (GPS); Goals, for courses; Inquiry instruction; Learning objective, in BoK; Learning objectives; Teaching; Teaching GIS&T; dept.egm